1995
DOI: 10.1038/ki.1995.308
|View full text |Cite
|
Sign up to set email alerts
|

Localization of mRNAs for insulin-like growth factor binding proteins 1 to 6 in rat kidney

Abstract: Insulin-like growth factor-I (IGF-I) is a peptide growth factor whose activity is modulated by interaction with the family of six IGF binding proteins (IGFBPs). IGF-I is detected in rat kidney and has metabolic and growth effects. We have used in situ hybridization to localize mRNAs for the IGFBPs in rat kidney. Messenger RNAs for all six IGFBPs were detected, each with a distinctive distribution. IGFBP-1 mRNA was expressed in the distal nephron, from the thick ascending limb of the loop of Henle to the cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 21 publications
3
23
0
Order By: Relevance
“…A complicating factor in matching our findings with the literature is that descriptions of changed IGF system expression patterns in renal disease models are scarce and, if existing, are often derived from rat studies where, compared with mice, differences in IGF system expression are observed, especially regarding IGFBP-1 expression (Chin et al 1992, Price et al 1995, Rabkin et al 1995, Lindenbergh-Kortleve et al 1997.…”
Section: Effects On Renal Expression Of Igf System Componentsmentioning
confidence: 66%
“…A complicating factor in matching our findings with the literature is that descriptions of changed IGF system expression patterns in renal disease models are scarce and, if existing, are often derived from rat studies where, compared with mice, differences in IGF system expression are observed, especially regarding IGFBP-1 expression (Chin et al 1992, Price et al 1995, Rabkin et al 1995, Lindenbergh-Kortleve et al 1997.…”
Section: Effects On Renal Expression Of Igf System Componentsmentioning
confidence: 66%
“…The remaining 20% of the IGFs are associated with IGFBP-1, -2, or -4 in a smaller complex, which can diffuse into the intravascular space, target IGFs to tissues, and modulate their bioavailability by inhibiting or potentiating their actions (21). In the kidney, IGFBPs are heterogeneously distributed to support their modulatory role in IGF actions (11,22,23). The overexpression of hIGFBP-1 in our transgenic mice (13.7 Ϯ 1.4 ng/mL and 3.0 Ϯ 0.4 ng/mL in homozygous and heterozygous mice, respectively) remained stable with age (14).…”
Section: Discussionmentioning
confidence: 99%
“…14 However IGFBP-1 mRNA is found in a small percentage of kidney cells, perhaps reflecting the lesser DNaseI hypersensitivity. 58 Weak liver specific sites at Ϫ800 (HS2) and Ϫ2,300 (HS3) were also detected. All sites were confirmed in several animals and with different restriction enzymes and probes (data not shown).…”
Section: Tissue-specific Dnasei Hypersensitivity Sites Within the Igfmentioning
confidence: 99%